Emerging Role of Higher Education for Human and Social Development - Soni, Rashmi (JOURNAL OF INDIAN EDUCATION, 2010)
As centers of production and dissemination of knowledge and training, higher education institutions are well positioned to link the local and the global. This gives them considerable access to and influence over change processes in many societies; this enhances their potential to contribute to human and social development. They are therefore, called upon to play a fundamental role in building the society.The paper throws light on the emerging role of Higher Education for human and social development. It has tried to highlight some strategies, actions and plans for reforms in university curriculum, teaching methodology and consideration of new approaches to education and social involvement. This is a crucial moment to revisit the role of higher education, starting with the present and the past, to project visions for the future. University-society interface can help in tackling social problems that lead to overall social development.